Medical Personnel Legal Protection Against Medical Dispute Settlement Efforts Viewed From Criminal Law - Sutedja, Ade Armada; Purwoko, A. Joko; Sumarwanto, Edi (Soepra Jurnal Hukum Kesehatan, 2023)
Medical dispute resolution efforts are the implementation of legal protection for medical personnel. A medical worker who is affected by a medical dispute can enter into the realm of civil (court), criminal (police), professional ethics (MKEK), professional discipline (MKDKI) together. Whereas in carrying out the activities of the medical profession, a doctor has the right to personal protection, honor, dignity, and is entitled to a sense of security and protection from the threat of fear to do or not do something which is a human right guaranteed by the Constitution. By using the normative juridical method of this paper, legal protection for medical personnel in the resolution of medical disputes is seen from the current legal certainty. Medical crimes and the protection of medical personnel have been regulated in the Criminal Code, Law No. 29 of 2004 on Medical Practice, Law No. 36 of 2009 on Health and Law No. 44 of 2009 on Hospitals. Settlement of medical criminal disputes can be through litigation and non-litigation, but there is an empty space in the legal protection of medical criminal disputes because there are no laws and regulations that regulate it even though it has been carried out, namely by penal mediation.